Hollow microspheres of polypyrrole/magnetite/carbon nanotubes by spray-dry as an electromagnetic synergistic microwave absorber. (30th April 2021) - Zhang, Mao; Qian, Xiang; Zeng, Qingwen; Zhang, Yahui; Cao, Hui; Che, Renchao
Abstract: Combining dielectric and magnetic components has been regarded as a promising way to develop functional materials with outstanding microwave absorption (MA) performance. However, it remains a tremendous challenge to assemble multi components into an integrated composite with suitable impedance matching via conventional wet chemical methods. Herein, ternary polypyrrole@Fe3 O4 /carbon nanotubes (PPy@Fe3 O4 /CNTs) microspheres with special hollow structure were successfully fabricated via a facile spray-dry method, which can realize rational assembly of magnetic and dielectric components. Hollow PPy@Fe3 O4 /CNTs spheres simultaneously avoid the agglomeration of magnetic particles while achieve the synergistic absorption. The maximum reflection loss of PPy@Fe3 O4 /CNTs absorber reached −51.8 dB at 8.8 GHz at the thickness of 2.38 mm. The relationship among components, structure and MA performance was also studied. As MA units, multi-component PPy@Fe3 O4 /CNTs microspheres effectively combine conductive polymer (PPy), strong magnetic Fe3 O4 and high-conductivity CNTs. Thus, the composite gains the advantage of complementation of dielectric, magnetic and conductive loss. Meanwhile, reasonable assembling of different components constructs abundant interfaces which can enhance dielectric polarization and hence improve absorption capacity. The special structure optimizes the distribution of CNTs, helping the composites to achieve better impedance matching. Overall, this work introduces an excellent microwave absorber and gives a new thought of material design. Graphical abstract: Image 1